Patterns of behavior and youth cultural prejudice of HIV: a study with Nicaraguan college students - Pérez-Pérez, Itahisa; Morón-Marchena, Juan Agustín; Cobos-Sanchiz, David (Población y Salud en Mesoamérica, 2015)
Objectives: Determine the knowledge, attitudes and risk behaviours of the Nicaraguan college students in respect to HIV in order to develop proposals for the socio-educative improvement that allow controlling the pandemics in this context. Methods: This is a qualitative study developed in the Multidisciplinary Regional Faculty of Chontales (Autonomous University of Nicaragua-Managua). Two focal groups with students, interviews to key informants from the same faculty, and a focal group with experts from the Nicaraguan commission against HIV were conducted. Results: the social expectations of sexism represent a burden in terms of sex education. There is a clear gender differentiation in the explicit discourse about sex in general and about STD in particular. There are significative differences in the perception and knowledge between the rural and urban world. A big amount of prejudices, stereotypes and phobia of infection persists. Interpretation and conclusions: Sexism (machismo) influences sexual relations, particularly in the use of protection. The traditional culture makes it difficult to talk openly about sexuality with the family or between peers. Risk behaviours are not due to the lack of information but rather due to poor self-awareness.